Abundance and Diversity of Spiders in Lemor Botanical Garden, East Lombok - Hakim, Muhammad Alfianul; Ayun Pazira; Ariana Ashri Dewi; Baiq Hanifa Utami Mawan Putri (Yayasan Siti Widhatul Faeha, 2026)
Spiders play an important role in ecosystems as natural predators and can be used as indicators of environmental conditions. This study aimed to analyze the relative abundance and diversity index of spiders in the ex-situ and in-situ conservation areas of Kebun Raya Lemor, East Lombok. Data collection was conducted using the Visual Encounter Survey (VES) method with a 200-meter transect and a 20-meter observation width. Data analysis was performed using the relative abundance formula and the Shannon–Wiener diversity index. The results showed that in the ex-situ conservation area, 13 species from 6 families were recorded, whereas in the in-situ conservation area, 8 species from 5 families were found. The highest relative abundance in the ex-situ area was represented by Leiobunum vittatum and Argyrodes miniaceus, while the in-situ area was dominated by Leiobunum vittatum. The diversity index in the ex-situ area was 2.32, and in the in-situ area was 1.32, both of which are classified as moderate; however, the ex-situ area showed higher diversity than the in-situ area. These findings indicate that the ex-situ area has a more heterogeneous habitat that supports a more diverse and balanced spider community than the in-situ area.